STRATEGIC LEADERSHIP AND TEACHER PERFORMANCE THROUGH ORGANIZATIONAL CLIMATE IN WEST SERAM PUBLIC SCHOOLS - Uchan Manakane; Rudolf Kempa; Theresia Laurens (RADJA PUBLIKA, 2026)
Principal leadership plays a strategic role in shaping organizational climate and improving teacher performance, particularly in public schools facing resource constraints. This study aimed to analyze the principal’s strategic leadership practices, school organizational climate, and teacher performance based on professional practice at State Junior High School 6 of West Seram Regency. A qualitative case study design was employed to explore these phenomena within their natural context. Data were collected through in-depth interviews, observations, and document analysis and analyzed using inductive thematic analysis. The findings revealed that the principal implemented adaptive and participatory strategic leadership through contextual vision adjustment, collaborative decision-making, and teacher empowerment. These practices contributed to the development of an open, supportive, and collaborative organizational climate characterized by trust, effective communication, and professional support. Furthermore, the positive organizational climate enabled teachers to strengthen their professional performance through reflective practice, contextual pedagogical innovation, and commitment to student development. The study concludes that teacher performance is not directly determined by leadership policies but emerges through an ongoing organizational process shaped by strategic leadership and organizational climate. The findings provide both theoretical and practical insights into improving teacher performance in public schools, particularly those located in resource-constrained regional areas.